The proliferation of alternative film exhibition spaces in Istanbul: cultural segregation and urban cinephilia. Issue 2 (26th May 2020) - Kayhan Müldür, Sezen
Abstract : In the last decade, Istanbul witnessed the rapid proliferation of alternative film exhibition spaces such as museums, cafes, art and cultural centres in specific neighbourhoods. This increase is a result of mostly three forces: the monopoly of dominant distribution companies, authoritarian pressure of the government and urban transformation in Istanbul. These places provide space for censored films and are essentially important for independent and experimental films as well as documentaries and short films which have very limited or no theatrical release. On the other hand, their concentration in specific districts and that they target the audience with certain cultural capital is aggregate hierarchical clusters. Through analysing these alternative exhibition spaces in Istanbul, this study investigates the changing relationship between film exhibition, audience and the city. It discovers how urban transformation, authoritarian cultural policies and economic capital changed cinema-going and urban cinephilia in Istanbul. It suggests that while these alternative film exhibiton venues provide space for independent filmmakers, festivals and censored films, they also articulate to social hierarchy and cultural segregation.